ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMP KELAS VIII DITINJAU MOTIVASI BELAJAR - Sabrina, Fadya Putri; Utami, Rini (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
The purpose of this study is to evaluate students' willingness to learn mathematics by measuring their ability to solve mathematical problems in flat-sided geometric material. Qualitative descriptive research is employed in this research approach. The subjects were SMP Islam YMI Wonopringgo class VIII E students in the even semester of the 2023–2024 school year. Six of the 33 pupils were chosen at random depending on their levels of learning motivation—high, medium, and low. Tests, questionnaires, and interviews were used in the data collecting process. By doing data reduction, data display, and conclusion drawing, data were studied. Six students (18%) fell into the high motivation category, twenty students (61%) fell into the medium category, and seven students (21%) fell into the low category. Based on the degree of student learning motivation, Polya's indicators of problem-solving skills were used to build the analysis. According to the study's findings, students with high learning motivation can complete three indicators, those in the medium group can complete one, and students in the low category are not proficient in completing all of the indicators